Genome-Wide Association Study on Resistance to Stalk Rot Diseases in Grain Sorghum. Issue 6 (1st June 2015) - Adeyanju, Adedayo; Little, Christopher; Yu, Jianming; Tesso, Tesfaye
Abstract: Stalk rots are important biotic constraints to sorghum production worldwide. Several pathogens may be associated with the disease, but Macrophomina phaseolina and Fusarium thapsinum are recognized as the major causal organisms. The diseases become more aggressive when drought and high-temperature stress occur during grain filling. Progress in genetic improvement efforts has been slow due to lack of effective phenotyping protocol and the strong environmental effect on disease incidence and severity. Deployment of modern molecular tools is expected to accelerate efforts to develop resistant hybrids. This study was aimed at identifying genomic regions associated with resistance to both causal organisms. A sorghum diversity panel consisting of 300 genotypes assembled from different parts of the world was evaluated for response to infection by both pathogens. Community resources of 79, 132 single nucleotide polymorphic (SNP) markers developed on the panel were used in association studies using a multi-locus mixed model to map loci associated with stalk rot resistance. Adequate genetic variation was observed for resistance to both pathogens. Structure analysis grouped the genotypes into five subpopulations primarily based on the racial category of the genotypes. Fourteen loci and a set of candidate genes appear to be involved in connected functions controlling plant defense response. However, each associated SNP had relatively small effect on the traits, accounting for 19–30% of phenotypic variation. Linkage disequilibrium analyses suggest that significant SNPs are genetically independent. Estimation of frequencies of associated alleles revealed that durra and caudatum subpopulations were enriched for resistant alleles, but the results suggest complex molecular mechanisms underlying resistance to both pathogens.